The Decision of Discharging a Patient from the Hospital: Case (Neurological) Report with Legal Implications - Rishabh Kumar; Raj Kumar; Shailesh Tripathi; Rajesh Kumar Verma (Indian Journal of Neurosurgery)
Patient safety is an important aspect of patient care following the discharge from the hospital (having gone through the required treatment). A transition from hospital care to domestic care/community care to a discharged patient is another complex factor that might have a bearing in the decision-making of a treated/operated patient due for discharge. However, the pressure on premier government medical institutions to cater to the awaited patients of chronic and severe diseases remains a vital consideration to bail out the lives of impending threats. Delayed discharges may have a financial implication on the one hand and hospital-borne infections on the other hand, which may be difficult to treat in immune-compromised state/vulnerable subset of patients. Unplanned discharges without thoughtful planning may result in readmission and misappropriation of limited resources at medical institutions. A thorough explanation of risks, warnings, care, support system, need for readmission, accessibility, communication, and facilitat.ion remain important considerations while discharging the patient. However, limited high-level government medical centers and pressure to accommodate other sick patients may force treating clinicians to discharge the patients at optimal levels of their clinical recovery, in countries like India.